Mitigating Pt Loss in Polymer Electrolyte Membrane Fuel Cell Cathode Catalysts Using Graphene Nanoplatelet Pickering Emulsion Processing. (18th August 2022) - Park, Kyu‐Young; Sweers, Matthew E.; Berner, Ulrich; Hirth, Erhard; Downing, Julia R.; Hui, Janan; Mailoa, Jonathan; Johnston, Christina; Kim, Soo; Seitz, Linsey C.; Hersam, Mark C.
Abstract: Carbon‐supported Pt nanoparticles are the leading catalysts for the cathode oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells. However, these ORR catalysts suffer from poor electrochemical durability, particularly the loss of electrochemical surface area (ECSA) due to Pt nanoparticle dissolution and agglomeration. Here, Pt loss is mitigated through a Pickering emulsion‐processing strategy that employs graphene nanoplatelet dispersions stabilized by the polymer ethyl cellulose. The resulting graphene‐Pt/Vulcan carbon (Pt/C) catalysts exhibit superior durability and ECSA retention throughout an accelerated stress test compared with a commercial Pt/C standard catalyst, both in a diagnostic‐rotating disc electrode setup and in a membrane electrode assembly full cell. These graphene‐Pt/C catalysts also improve durability at high‐voltage conditions, providing further evidence of their exceptional electrochemical stability. Consistent with density functional theory calculations, postelectrochemical characterization reveals that Pt nanoparticles localize at graphene defects both on the basal plane and especially at the edges of the graphene nanoplatelets. Since this Pt nanoparticle localization suppresses Pt nanoparticle dissolution and agglomeration without hindering accessibility of the reactant species to the catalyst surface, the ORR performance under both idealized and practical experimental conditions shows significantly improved durability while maintaining high electrochemical activity. Abstract : This study mitigates Pt loss for the cathode oxygen reduction reaction in polymer electrolyte membrane fuel cells through a Pickering emulsion‐processing strategy that employs graphene nanoplatelet dispersions stabilized by the polymer ethyl cellulose. The resulting catalysts exhibit superior durability and electrochemical surface area retention compared with incumbent approaches.